PENGARUH FASILITAS BELAJAR DAN PERHATIAN ORANG TUA TERHADAP HASIL BELAJAR SELAMA PANDEMIC DI SMK KARANGANYAR - Aisyah Nurul Ichsan; Wiedy Murtini; Patni Ninghardjanti (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2022)
Abstract This research explained: (1) the impact of learning facilities on learning outcomes of staffing management students during the Covid-19 pandemic; (2) the impact of parental attention on learning outcomes of staffing management students during the Covid-19 pandemic; and (3) the impact of learning facilities and parental attention on learning outcomes of staffing management students during the Covid- 19 pandemic. This research is quantitative research with correlational method. The population were class XI students of the office management Vocational High School in Karanganyar. The proportionate stratified random sampling technique utilized and yielded 144 students from SMK Negeri 1 Karanganyar and SMK Muhammadiyah 2 Karanganyar. Questionnaires and documentation procedures used to obtain data. Multiple linear regression analysis with precondition tests used to analyze the data. The results of this study explained that: (1) there is a positive effect of learning facilities on learning outcomes during the pandemic (tcount8.450>ttable1.976); (2) there is a positive effect of parental attention on the learning outcomes during the pandemic (tcount 2.533 > ttable 1.976); (3) there is a positive effect between both on the learning outcomes of during the pandemic (Fcount 61.713>Ftable3.06). X1 and X2 have an influence of 46,7% on Y (R2=0,467).